APPLICATION OF REHABILITATION IN LAW ENFORCEMENT OF NARCOTICS CRIMES - Putri Melati, Dwi (LPPM, Universitas Muhammadiyah Riau, 2026)
Acts of narcotics abuse (narcotics-related crimes) are extraordinary crimes. Law Number 35 of 2009 concerning Narcotics explicitly stipulates that narcotics addicts are obliged to undergo medical and social rehabilitation. This provision reflects a paradigm shift in legal policy from a punitive approach to a therapeutic and restorative justice approach, where perpetrators are not only subject to criminal sanctions but are also directed to rehabilitation. This scientific paper uses a normative juridical method, because it focuses on analyzing the implementation of rehabilitation for narcotics-related offenders. Conceptually, the implementation of rehabilitation in narcotics law enforcement in Indonesia is supported by a strong legal foundation both at the national and international levels. Law No. 35 of 2009 concerning Narcotics, Supreme Court Circular Letter No. 4 of 2010, Joint Regulation of the National Narcotics Agency (BNN), National Police of the Republic of Indonesia, Attorney General's Office, and Ministry of Health (2014), as well as Government Regulation No. 25 of 2011—which regulates mandatory reporting mechanisms for narcotics addicts—serve as a clear normative basis for regulating the implementation of rehabilitation for narcotics addicts and abusers.